The same heterozygous Col4A4 mutation triggered different renal pathological changes in Chinese family members - Zhu, Fengming; Li, Yueqiang; Wang, Yuxi; Yao, Ying; Zeng, Rui (Frontiers in Genetics, 2023)
Background: Mutations in the collagen components of the glomerular basement membrane (GBM) often lead to hereditary glomerulonephritis. Previous studies have identified that autosomal dominant mutations of Col4A3, Col4A4 or Col4A5 are associated with thin basement membrane nephropathy (TBMN), Alport syndrome and other hereditary kidney diseases. However, the genetic mutations underlying other glomerulonephritis types have not been elucidated. Methods: In this study, we investigated a Chinese family with hereditary nephritis using the methods of genetic sequencing and renal biopsy. Genomic DNA was extracted from peripheral blood of the proband and her sister, and subsequently was performed genetic sequencing. They were found to have the similar mutation sites. Other family members were then validated using Sanger sequencing. The proband and her sister underwent renal puncture biopsies, and experienced pathologists performed PAS, Masson, immunofluorescence, and immunoelectron microscopic staining of the kidney tissue sections. Results: Through genetic sequencing analysis, we detected a novel heterozygous frameshift mutation c.1826delC in the COL4A4 (NM_000092.4) gene coding region, and 1 hybrid missense variation c.86G>A (p. R29Q) was also detected in the TNXB (NM_019105.6) gene coding region in several members of this Chinese family. Interestingly, we found that the same mutations caused different clinical features and distinct pathological changes in individual family members, which confirmed that pathological and genetic testing are crucial for the diagnosis and treatment of hereditary kidney diseases. Conclusion: In this study, we found a novel heterozygous mutation in Col4A4 and co-mutations of the TNXB gene in this Chinese family. Our study indicated that the same Col4A4 mutated variants produced different pathological and clinical changes in different family members. This discovery may provide novel insights into the study of hereditary kidney disease. In addition, new genetic biology techniques and renal biopsy of individual family members are essential.